STUDY ON THE IMPORTANCE OF PHYSICAL EDUCATION IN TODAY'S SCHOOLS - BENEDEK FLORIAN (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
The purpose of this research study is to help connect the program to its long-term impact in a sample population school. Some research efforts have determined this, different aspects of health behavior exceed participation in physical education classes, they are discussed below. Although many research has established the long-term generalized benefits of attending physical education classes, a limited number of research studies have examined the long-term effects of physical education in high school. Physical education offers students many opportunities to improve their overall lifestyle. First, it gives students the opportunity to improve their physical skills, physical development and health. The purpose of this study was to investigate the effects of school physical activity on a physical education program in a post-secondary school environment. The three major areas that this study investigated were: a) students' perceptions of physical education in today's schools; b) motivation of physical education teachers to improve training; c) characteristics of an effective physical education programme.